Leadership implicit theories, LMX and employment wellbeing: Generalization of a theoretical model - Nader, Martín (2010)
The generalizability of a theoretical model is studied in several regions of Argentina. Participants were 1009 people (440 men and 569 women) from four regions. We analyzed the differences in the variable values at work to confirm if the regions were culturally different from each other. Next we designed a theoretical model where the variables were: discrepancy between implicit theories, quality of relationship with the superior and wellbeing in the organization. Results showed that the four regions displayed differences on values orientations. The Northwest and Patagonia regions showed the greatest differences in comparison with the two remaining regions. The model is partially generalizable since there are differences between regions in some of the proposed theoretical relations.